Design and fabrication of folding table - Mohd Rosdi, Hussin (2009)
Manufacturing process is a process of converting raw material into product. It can be described the transformation of materials into terms of greater value by means of one or more processing and/or assembly operations. The study of manufacturing was very important in order to carry out this project to ensure that student understand on what are needs to do. This project is focused on designing and fabricating the Folding Table. The main objective in this project is to design and fabricate the Folding Table which can be fold easily and can be store into the small space. This project involves the process of designing the Folding table by considering the shape, functionality, portability for people to use it and the manufacturing cost. The material of this design is easy to gain it, because it only using rectangular hollow steel and aluminium. So that the method joining that can be compatible in assembled this Folding Table is welding process and joining the aluminium to the frame is by using rivet. This project also required analysis to ensure the strength and safety of the product meet the user need. After all processes had done, the development of this Folding Table may help us to understand the fabrication and designing process involved in this project. The manufacturing process included in this project is marking and cutting of material, machining, drilling, rivet , joining and finishing.